Therapeutic Protection Against H. pylori Infection in Mongolian Gerbils by Oral Immunization With a Tetravalent Epitope-Based Vaccine With Polysaccharide Adjuvant - Guo, Le; Hong, Dantong; Wang, Shue; Zhang, Fan; Tang, Feng; Wu, Tao; Chu, Yuankui; Liu, Hongpeng; He, Meng; Yang, Hua; Yin, Runting; Liu, Kunmei (Frontiers in Immunology, 2019)
Urease is an effective target for design of a therapeutic epitope vaccine against Helicobacter pylori (H. pylori). In our previous studies, an epitope vaccine CTB-UE containing Th and B epitopes from H. pylori urease was constructed, and the CTB-UE vaccine could provide therapeutic effect on H. pylori infection in mice. However, a multivalent vaccine, combining different antigens participating in different aspects of H. pylori colonization and pathogenesis, may be more effective as a therapeutic vaccine than a univalent vaccine targetting urease. Therefore, a multivalent epitope vaccine FVpE, containing Th1-type immune adjuvant NAP, three selected functional fragments from CagA and VacA, and an urease multi-epitope peptide (UE) from CTB-UE, was constructed in this study and expected to obtain better sterilizing immunity than the univalent epitope vaccine CTB-UE. The therapeutic effect of multivalent epitope vaccine FVpE with polysaccharide adjuvant (PA) was evaluated in H. pylori-infected Mongolian gerbil model. The results showed that both FvpE and CTB-UE vaccine could induce similar levels of specific antibodies against H. pylori urease, and had similar inhibition effect on H. pylori urease activity. However, only FVpE could induce high levels of specific antibodies to CagA, VacA and NAP. In addition, oral therapeutic immunization with FVpE plus PA significantly reduced the number of H. pylori colonies in the stomach of Mongolian gerbils compared with oral immunization with CTB-UE plus PA, or FVpE only, and the FVpE vaccine with PA even exhibited sterilizing immunity. The protection of FVpE was related to the mixed CD4+ T cell responses and epitope-specific antibodies against various H. pylori antigens. These results indicate that a multivalent epitope vaccine targetting various H. pylori antigens could be a promising candidate against H. pylori infection.